Termiticidal activity of chitosan against the subterranean termites Reticulitermes flavipes and Reticulitermes virginicus1. Issue 7 (9th March 2018) - Raji, Olanrewaju; Tang, Juliet D; Telmadarrehei, Telmah; Jeremic, Dragica
Abstract: BACKGROUND: Chitosan is a derivative form of chitin, which is the major component of exoskeletons of arthropods and the cell walls of fungi. The antimicrobial activity of chitosan against lepidopterans, aphids, fungi and bacteria has been extensively investigated, but only one report on the termiticidal effect of chitosan on termites has been published. In this study, we examined the termiticidal activity of chitosan by exposing single colonies of Reticulitermes flavipes (Kollar) and Reticulitermes virginicus Banks to wood treated with six different concentrations of chitosan solutions. Termite mortality and percent mass loss of wood samples after exposure to termites for 4 weeks were calculated. RESULTS: High termite mortality (≥ 94%) occurred during exposure of R. flavipes termites to chitosan‐treated wood with ≥38 mg g ‐1 treatment concentrations (≥ 2% chitosan), while <50% termite mortality was observed at lower treatment concentrations (11–15 mg g ‐1 ; 0.5% and 1% chitosan). For R. virginicus, 100% mortality was observed at all levels of treatment concentrations. A decrease in the percent mass loss of the wood sample was apparent in samples treated with solutions with an increasing chitosan concentration, with a significant difference ( P  < 0.05) between lower and higher treatment concentrations. Treatment retention in wood samples upon leaching was also determined and showed retention levels of between 0 and 30 mg g ‐1 chitosan retention. CONCLUSION: This study investigated the exposure of subterranean termites to chitosan as a wood preservative. The results show that chitosan treatments at sufficiently high loadings could protect wood against termites, preferably under non‐leaching conditions. © 2018 Society of Chemical Industry Abstract : A knowledge gap exists for the termiticidal properties of chitosan against subterranean termites, Reticulitermes spp., and this study aimed to elucidate its toxicity to the termites.